BIOREMEDIATION: A SUPERIOR ALTERNATIVE FOR REMEDIATING TANNERY EFFLUENT-CONTAMINATED SOIL (FUDMA JOURNAL OF SCIENCES, 2025)
Tannery effluent poses significant risks to soil health, primarily through contamination with heavy metals like chromium, sulphides, and persistent organic pollutants (POPs). These toxic substances inhibit microbial activity, reducing nutrient cycling and organic matter decomposition essential for soil fertility. Beneficial microorganisms, including nitrogen-fixing bacteria, are particularly affected, leading to altered microbial communities dominated by less advantageous, metal-tolerant species. Accumulation of POPs and heavy metals disrupts soil enzymatic activities, interferes with plant root growth, and complicates remediation efforts due to pollutant migration to groundwater and potential entry into the food chain. Prolonged exposure to such contaminants diminishes soil fertility, reduces resilience, and disrupts ecosystem services, posing threats to agricultural productivity and environmental health. This review was aimed to outline what made bioremediation a superior treatment technology among other methods used in remediating tannery effluent contaminated soil. Efforts to mitigate tannery effluent impacts involve a combination of physical, chemical, and biological remediation technologies. Physical methods like soil washing, flushing, and thermal desorption focus on removing or isolating contaminants, while chemical approaches such as oxidation, reduction, and stabilization transform pollutants to less harmful forms or immobilize them. Biological remediation leverages microorganisms and plants to detoxify contaminants sustainably. Bioremediation strategies with aid of bioaugmentation and biostimulation do enhance microbial activity to address organic and inorganic pollutants effectively more than physical and chemical methods. Another excellent bioremediation technology called phytoremediation can also address organic and inorganic pollutants effectively, Achieving better remediation technique should be coupled with stringent industrial regulations, sustainable tanning methods, and stakeholder awareness
Keywords: Soil washing; Thermal desorption; Bioremediation; Phytoremediation; Chromium; Persistent Organic Pollutants (POPs)